The valorization of the functional potential of tomato processed waste - Utpalakshya Das; Subhajit Ray (International Journal on Food, Agriculture and Natural Resources, 2022)
This investigation aimed to undertake an effective waste management strategy by valorizing the functional potential of thermally processed tomato processed waste fragments collected from three different zones of different states of India viz. Shillong (Sample A, Meghalaya), Falakata (Sample B, West Bengal), and Jalpaiguri (Sample C, West Bengal). Thermal processing of fragmented waste samples prior to the extraction process was carried out with three different drying techniques viz. solar drying, hot air oven drying, and combined drying. The experimental investigation with a comparative design revealed that the total phenolic content (TPC), lycopene content, and β-carotene content of solar dried waste fragments derived from samples A & B are significantly higher than those in sample C. Moreover, the sun-dried  pomace fraction of tomato waste contains the maximum amount of bioactive components viz. lycopene (303.452mg/kg in sample A, 297.96 mg/kg in sample B, and 203.583 mg/kg in sample C),  β-carotene content (299.6mg/kg in sample B, 299.1mg/kg in sample A, and 223.004 mg/kg in sample C) and total phenolic content (6.8698mg/kg in sample B, 5.9541mg/kg in sample A, and 5.7915mg/kg in sample C) followed by skin lycopene (282.297mg/kg in sample A, 276.8 mg/kg in sample B, and 182.603 mg/kg in sample C); β-carotene (280.41mg/kg in sample A, 278.002mg/kg in sample B, and 188.258 mg/kg in sample C) and total phenolics (6.4413mg/kg in sample B, 5.2633mg/kg in sample A, and 5.0223mg/kg in sample C) and seed lycopene (276.8mg/kg in sample B, 86.746 mg/kg in sample A, and 62.163mg/kg in sample C); β- carotene (85.23mg/kg in sample B, 84.01mg/kg in sample A, and 66.23mg/kg in sample C) and total phenolics (5.9228mg/kg in sample B followed by 4.6602mg/kg in sample A and 4.641mg/kg) respectively. The solar drying technique is considered to be a novel pretreatment process compared to other treatments e.g., oven drying, and combined drying, in the efficacy of extraction of bioactive components from tomato processed waste fractions due to its lower impact on heat-sensitive biomaterials.